Changes in Indian Agriculture: Trends, Challenges, and Future Prospects Pargat Kaswan Indian agriculture has undergone transformative changes over the past several decades, shaped by technological advancements, policy shifts, climate variability, and so (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Indian agriculture has undergone transformative changes over the past several decades, shaped by technological advancements, policy shifts, climate variability, and socio-economic dynamics. From the Green Revolution that ensured food security to the current focus on sustainable and digital agriculture, the sector has continuously adapted to emerging challenges and opportunities. However, Indian farmers still face critical issues such as fragmented landholdings, declining soil fertility, water scarcity, and price volatility. This paper examines the historical and contemporary changes in Indian agriculture, analyzes the major challenges affecting the sector, and explores future opportunities like precision farming, organic agriculture, agripreneurship, and digital innovations. The study also discusses policy interventions necessary for ensuring long-term agricultural sustainability and inclusive growth.